Method for treating and recycling cooling water

Through the phosphorus-free composite scale inhibitor, the synergistic effect of composite copolymers and other components is used to solve the problems of scale precipitation and metal corrosion in industrial cooling water, achieving efficient scale inhibition and corrosion inhibition effects, suitable for high-temperature and high salinity environments.

CN119591261AActive Publication Date: 2025-03-11HANGZHOU HUINENG IND CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411932866.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-11
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

During the recycling of industrial cooling water, it often faces problems such as inorganic salt deposition, metal corrosion, and bacterial and algae microorganism breeding, resulting in reduced system operation efficiency. Traditional organic phosphine scale inhibitors are not effective in precipitation of various scales and contain environmentally unfriendly phosphorus substances.

Method used

A phosphorus-free composite scale inhibitor is used, which consists of a composite copolymer, octylphenol polyoxyethylene ether, glycerin, tetrasodium ethylenediaminetetraacetate and zinc salt. It forms a polymer through double bond addition reaction, and coordinate chelation of carboxyl, hydroxyl, sulfonic acid group and calcium ions to inhibit scale precipitation and metal corrosion.

Benefits of technology

In the case of small amount of use, this composite scale inhibitor can effectively disperse high-concentration calcium ions, magnesium ions, iron ions and sulfate particles, significantly improve scale inhibition effect, slow down metal corrosion rate, and adapt to high-temperature and high salinity environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005210782580000091
    Figure BDA0005210782580000091
Patent Text Reader

Abstract

The invention relates to the technical field of industrial cooling water treatment, and particularly discloses a method for treating and recycling cooling water, compared with an existing scale inhibitor, the composite scale inhibitor provided by the invention has the characteristics of high efficiency and environmental protection, does not adopt any phosphorus-containing substance in the components, does not cause secondary damage to water quality, and has a good application prospect. Under the synergistic effect of a plurality of components, scale-forming particles such as high-concentration calcium ions and magnesium ions can be dispersed under the condition that the usage amount is very small, and the scale inhibitor has an excellent scale inhibition effect; the composite copolymer provided by the invention can form a very strong coordination effect with the surface of the steel, in the corrosion process, carboxymethyl chitosan and a double bond addition reaction product can form a compact and stable polymer film on the surface of the steel, and under the combined action of carboxymethyl chitosan and the double bond addition reaction product, a corrosion phenomenon caused by direct contact between a corrosion medium and the surface of the steel is prevented; the metal is protected from being corroded by harmful media, and a good corrosion inhibition effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of industrial cooling water treatment, and in particular to a method for treating and reusing cooling water. Background Art

[0002] In the process of recycling industrial cooling water, there are often many problems such as inorganic salt deposition, metal corrosion, and the growth of bacteria and algae, which seriously affect the normal operation efficiency of the system. Over time, due to the accumulation of inorganic salts such as calcium carbonate, calcium sulfate and barium sulfate dissolved in water, these substances will gradually deposit on the inner surface of the pipe, forming thick calcium scale, which will hinder the flow of cooling water, resulting in a significant reduction in the heat exchange efficiency of the heat exchange equipment, which may cause insufficient heat exchange capacity of the entire cooling system. In addition, the adhesion of calcium scale not only reduces the surface area of ​​heat exchange, but also may cause pipe blockage, increase the difficulty and cost of system maintenance, and even cause equipment damage and production suspension in severe cases.

[0003] In the process of circulating cooling water operation, adding corrosion and scale inhibitors is one of the important methods to stabilize water quality and inhibit corrosion and scale. Currently, most commonly used corrosion and scale inhibitors are phosphorus-containing formulas. Since phosphorus is one of the main causes of eutrophication of water bodies, the state strictly controls the total phosphorus index in the external drainage of enterprises. Phosphorus-free and low-phosphorus corrosion and scale inhibitors have become a new direction for the research and development of water treatment agents.

[0004] Chinese patent document CN102838215A discloses a composite scale inhibitor composed of polyepoxysuccinic acid, ethylenediaminetetramethylenephosphonic acid, itaconic acid-maleic acid-acrylic acid-methyl acrylate polymer and dendritic polyamide-amine; the weight percentage of each component of the scale inhibitor is: polyepoxysuccinic acid 22-32%, ethylenediaminetetramethylenephosphonic acid 10-18%, itaconic acid-maleic acid-acrylic acid-methyl acrylate polymer 35-50%, dendritic polyamide-amine 10-18%, and the rest is water. Practice has shown that these traditional organic phosphine scale inhibitors and anionic polymer scale inhibitors and dispersants cannot simultaneously play a good scale inhibition effect on amorphous SiO2 scale precipitation, calcium carbonate scale, calcium sulfate scale, etc., but the above-mentioned composite scale inhibitor contains phosphorus and is not environmentally friendly. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for treating and reusing cooling water. The composite scale inhibitor provided by the present invention does not contain phosphorus and has excellent scale inhibition and corrosion inhibition properties.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme:

[0007] A method for treating and reusing cooling water, the method comprising adding a composite scale inhibitor to the cooling water, wherein the composite scale inhibitor comprises the following raw materials in terms of mass percentage: 10-15% of a composite copolymer, 5-10% of octylphenol polyoxyethylene ether, 3-6% of glycerol, 2-4% of tetrasodium ethylenediaminetetraacetate, 1-3% of zinc salt, and the remainder being deionized water;

[0008] The preparation method of the composite copolymer is as follows:

[0009] Carboxymethyl chitosan, 1-vinyl-3-methylimidazole p-toluenesulfonate and methacryloylethyl sulfobetaine are added to deionized water, stirred evenly, nitrogen is introduced to expel the air, the system is heated to 65-75° C., and then an initiator is added, stirred to react, and after the reaction is completed, cooled to room temperature and vacuum freeze-dried to obtain a composite copolymer.

[0010] On the basis of the above technical solution, specifically, the addition amount of the composite scale inhibitor is 10-40 mg / L, for example, 10 mg / L, 15 mg / L, 20 mg / L, 25 mg / L, 30 mg / L, 35 mg / L, 40 mg / L can be selected, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0011] On the basis of the above technical scheme, specifically, the mass ratio of carboxymethyl chitosan, 1-vinyl-3-methylimidazole p-toluenesulfonate, methacryloylethyl sulfobetaine and initiator is 10-20:4-8:3-6:0.5-1.

[0012] More specifically, the initiator is selected from persulfates, for example, potassium persulfate, sodium persulfate or ammonium persulfate.

[0013] On the basis of the above technical scheme, specifically, the stirring reaction temperature is 65-75°C, for example, 65°C, 68°C, 70°C, 72°C, 75°C can be selected; the stirring reaction time is 2-4h, for example, 2h, 2.5h, 3h, 3.5h, 4h can be selected, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] On the basis of the above technical solution, specifically, the zinc salt is selected from zinc nitrate or zinc chloride.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] (1) Compared with existing scale inhibitors, the composite scale inhibitor provided by the present invention has the characteristics of high efficiency and environmental protection. Its components do not use any phosphorus-containing substances and will not cause secondary damage to water quality. Moreover, under the synergistic effect of multiple components, it can disperse high-concentration scale-forming particles such as calcium ions, magnesium ions, iron ions, sulfate ions, etc. with a very small amount of use, and has an excellent scale inhibition effect.

[0017] (2) The present invention forms a polymer by a double bond addition reaction between 1-vinyl-3-methylimidazole toluenesulfonate and methacryloylethyl sulfobetaine. During the addition reaction, the hydroxyl groups in carboxymethyl chitosan interact with the carboxyl groups and sulfonic acid groups in the polymer through hydrogen bonds, and the carboxymethyl chitosan is embedded in the molecular chain of the polymer, thereby obtaining a composite copolymer. The carboxyl groups, hydroxyl groups, and sulfonic acid groups in the composite copolymer can coordinate and chelate with calcium ions, so that the composite copolymer can be adsorbed on the surface of calcium carbonate and calcium phosphate crystals, inhibiting the crystallization of calcium carbonate and calcium phosphate to form crystal scale, slowing down the growth rate of the crystals, increasing the repulsive force between the crystals, and preventing them from aggregating, thereby making the generated scale soft and easy to be washed away by water flow, thereby achieving a good scale inhibition effect.

[0018] (3) The composite copolymer provided by the present invention can form a strong coordination effect with the surface of steel. During the corrosion process, carboxymethyl chitosan and the double bond addition reaction product can form a dense and stable polymer film on the surface of the steel. Under the joint action of the two, the corrosive medium is prevented from directly contacting the steel surface and causing corrosion, thereby protecting the metal from corrosion by harmful media, thereby slowing down the corrosion rate of the metal and achieving a good corrosion inhibition effect. At the same time, the composite copolymer contains carboxymethyl chitosan, imidazole groups and benzene ring structures, has strong thermal stability, can adapt to high temperature and high salinity environments, and meet the requirements of on-site production. DETAILED DESCRIPTION

[0019] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.

[0020] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.

[0021] The model of octylphenol polyoxyethylene ether used in the embodiments of the present invention is OP-10, purchased from Yixing Jiateng Chemical Co., Ltd.; the CAS number of carboxymethyl chitosan is 83512-85-0, purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.; the CAS number of 1-vinyl-3-methylimidazole p-toluenesulfonate is 187387-86-6; the CAS number of methacryloylethyl sulfobetaine is 3637-26-1, purchased from Shanghai Yuanye Biotechnology Co., Ltd.

[0022] Example 1

[0023] This embodiment is used to illustrate the method for treating and reusing cooling water provided by the present invention.

[0024] The cooling water used in this embodiment is simulated industrial cooling water, pH = 8.3, conductivity 946.9μS / cm, total hardness (calcium carbonate) 74.68mg / L, calcium hardness 36.27mg / L, total alkalinity 58.4mg / L, chloride ion 76.82mg / L, sulfate 56.64mg / L.

[0025] A composite scale inhibitor is added to the cooling water, the dosage of the composite scale inhibitor is 10 mg / L, and the composite scale inhibitor includes the following raw materials in terms of mass percentage: 10% composite copolymer, 10% octylphenol polyoxyethylene ether, 5% glycerol, 3% tetrasodium ethylenediaminetetraacetic acid, 2% zinc chloride, and the rest is deionized water.

[0026] Wherein, the preparation method of the composite copolymer is as follows:

[0027] 10 g of carboxymethyl chitosan, 4 g of 1-vinyl-3-methylimidazole p-toluenesulfonate and 3 g of methacryloylethyl sulfobetaine were added to 100 mL of deionized water, stirred evenly, nitrogen was introduced to expel the air, the system was heated to 70°C, and then 0.5 g of initiator ammonium persulfate was added, and the reaction was stirred at 70°C for 3 h. After the reaction was completed, the mixture was cooled to room temperature and vacuum freeze-dried to obtain a composite copolymer.

[0028] Example 2

[0029] This embodiment is used to illustrate the method for treating and reusing cooling water provided by the present invention.

[0030] The cooling water used in this embodiment is simulated industrial cooling water, pH = 8.3, conductivity 946.9μS / cm, total hardness (calcium carbonate) 74.68mg / L, calcium hardness 36.27mg / L, total alkalinity 58.4mg / L, chloride ion 76.82mg / L, sulfate 56.64mg / L.

[0031] A composite scale inhibitor is added to the cooling water, the dosage of the composite scale inhibitor is 20 mg / L, and the composite scale inhibitor includes the following raw materials in terms of mass percentage: 15% composite copolymer, 8% octylphenol polyoxyethylene ether, 6% glycerol, 4% tetrasodium ethylenediaminetetraacetic acid, 3% zinc chloride, and the rest is deionized water.

[0032] Wherein, the preparation method of the composite copolymer is as follows:

[0033] 20 g of carboxymethyl chitosan, 8 g of 1-vinyl-3-methylimidazole p-toluenesulfonate and 6 g of methacryloylethyl sulfobetaine were added to 150 mL of deionized water, stirred evenly, nitrogen was introduced to expel the air, the system was heated to 70° C., and then 1 g of initiator ammonium persulfate was added, and the reaction was stirred at 70° C. for 3 h. After the reaction was completed, the mixture was cooled to room temperature and vacuum freeze-dried to obtain a composite copolymer.

[0034] Example 3

[0035] This embodiment is used to illustrate the method for treating and reusing cooling water provided by the present invention.

[0036] The cooling water used in this embodiment is simulated industrial cooling water, pH = 8.3, conductivity 946.9μS / cm, total hardness (calcium carbonate) 74.68mg / L, calcium hardness 36.27mg / L, total alkalinity 58.4mg / L, chloride ion 76.82mg / L, sulfate 56.64mg / L.

[0037] A composite scale inhibitor is added to the cooling water, the dosage of the composite scale inhibitor is 30 mg / L, and the composite scale inhibitor includes the following raw materials in terms of mass percentage: 15% composite copolymer, 8% octylphenol polyoxyethylene ether, 6% glycerol, 4% tetrasodium ethylenediaminetetraacetic acid, 3% zinc chloride, and the rest is deionized water.

[0038] Wherein, the preparation method of the composite copolymer is as follows:

[0039] 15 g of carboxymethyl chitosan, 6 g of 1-vinyl-3-methylimidazole p-toluenesulfonate and 5 g of methacryloylethyl sulfobetaine were added to 150 mL of deionized water, stirred evenly, nitrogen was introduced to expel the air, the system was heated to 70° C., and then 0.8 g of initiator ammonium persulfate was added, and the reaction was stirred at 70° C. for 3 h. After the reaction was completed, the mixture was cooled to room temperature and vacuum freeze-dried to obtain a composite copolymer.

[0040] Example 4

[0041] This embodiment is used to illustrate the method for treating and reusing cooling water provided by the present invention.

[0042] The cooling water used in this embodiment is simulated industrial cooling water, pH = 8.3, conductivity 946.9μS / cm, total hardness (calcium carbonate) 74.68mg / L, calcium hardness 36.27mg / L, total alkalinity 58.4mg / L, chloride ion 76.82mg / L, sulfate 56.64mg / L.

[0043] A composite scale inhibitor is added to the cooling water, the dosage of the composite scale inhibitor is 40 mg / L, and the composite scale inhibitor includes the following raw materials in terms of mass percentage: 12% composite copolymer, 8% octylphenol polyoxyethylene ether, 3% glycerol, 2% tetrasodium ethylenediaminetetraacetic acid, 1% zinc chloride, and the rest is deionized water.

[0044] Wherein, the preparation method of the composite copolymer is as follows:

[0045] 15 g of carboxymethyl chitosan, 6 g of 1-vinyl-3-methylimidazole p-toluenesulfonate and 5 g of methacryloylethyl sulfobetaine were added to 150 mL of deionized water, stirred evenly, nitrogen was introduced to expel the air, the system was heated to 70° C., and then 0.8 g of initiator ammonium persulfate was added, and the reaction was stirred at 70° C. for 3 h. After the reaction was completed, the mixture was cooled to room temperature and vacuum freeze-dried to obtain a composite copolymer.

[0046] Comparative Example 1

[0047] This comparative example is used to illustrate the method for treating and reusing cooling water provided by the present invention.

[0048] The cooling water used in this comparative example is simulated industrial cooling water, pH = 8.3, conductivity 946.9μS / cm, total hardness (calcium carbonate) 74.68mg / L, calcium hardness 36.27mg / L, total alkalinity 58.4mg / L, chloride ion 76.82mg / L, sulfate ion 56.64mg / L.

[0049] A composite scale inhibitor is added to the cooling water, the dosage of the composite scale inhibitor is 30 mg / L, and the composite scale inhibitor includes the following raw materials in terms of mass percentage: 15% carboxymethyl chitosan, 8% octylphenol polyoxyethylene ether, 6% glycerol, 4% tetrasodium ethylenediaminetetraacetic acid, 3% zinc chloride, and the rest is deionized water.

[0050] Compared with Example 3, Comparative Example 1 uses carboxymethyl chitosan to replace the composite copolymer.

[0051] Comparative Example 2

[0052] This comparative example is used to illustrate the method for treating and reusing cooling water provided by the present invention.

[0053] The cooling water used in this comparative example is simulated industrial cooling water, pH = 8.3, conductivity 946.9μS / cm, total hardness (calcium carbonate) 74.68mg / L, calcium hardness 36.27mg / L, total alkalinity 58.4mg / L, chloride ion 76.82mg / L, sulfate ion 56.64mg / L.

[0054] A composite scale inhibitor is added to the cooling water, the dosage of the composite scale inhibitor is 30 mg / L, and the composite scale inhibitor includes the following raw materials in terms of mass percentage: 15% composite copolymer, 8% octylphenol polyoxyethylene ether, 6% glycerol, 4% tetrasodium ethylenediaminetetraacetic acid, 3% zinc chloride, and the rest is deionized water.

[0055] Wherein, the preparation method of the composite copolymer is as follows:

[0056] 6 g of 1-vinyl-3-methylimidazole p-toluenesulfonate and 5 g of methacryloylethyl sulfobetaine were added to 150 mL of deionized water, stirred evenly, nitrogen was introduced to expel the air, the system was heated to 70° C., and then 0.8 g of initiator ammonium persulfate was added. The mixture was stirred and reacted at 70° C. for 3 h. After the reaction was completed, the mixture was cooled to room temperature and vacuum freeze-dried to obtain a composite copolymer.

[0057] Compared with Example 3, in Comparative Example 2, no carboxymethyl chitosan was added to the composite copolymer.

[0058] Calcium carbonate scale inhibition test: Tested in accordance with GB / T 16632-2019 "Determination of scale inhibition performance of water treatment agents-Calcium carbonate deposition method" standard;

[0059] Calcium phosphate scale inhibition test: Tested in accordance with GB / T 22626-2008 "Determination of scale inhibition performance of water treatment agents - Calcium phosphate deposition method";

[0060] The test results are shown in Table 1.

[0061] Table 1 Scale inhibition performance test results

[0062]

[0063]

[0064] Corrosion inhibition performance test: According to GB / T18175-2014 standard, the hanging piece material is Q245R, the test temperature is 80°C, the test time is 72h, the stirring line speed is 0.33m / s, and the test results are shown in Table 2.

[0065] Table 2 Corrosion inhibition performance test results

[0066] Corrosion rate (mm / a) Example 1 0.021 Example 2 0.019 Example 3 0.014 Example 4 0.013 Comparative Example 1 0.072 Comparative Example 2 0.047

[0067] As can be seen from Table 2, in Comparative Example 1, carboxymethyl chitosan is used to replace the composite copolymer, and in Comparative Example 2, no carboxymethyl chitosan is added to the composite copolymer, and the addition amount of the composite copolymer remains unchanged. The corrosion inhibition effects of Comparative Examples 1 and 2 are not as good as those of the embodiments of the present invention. It can be seen that the components in the composite copolymer provided by the present invention have a synergistic effect and together play a good corrosion inhibition effect.

[0068] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modification or improvement made without departing from the spirit of the present invention belongs to the scope of protection claimed in the present invention.

Claims

1. A method for treating and reusing cooling water, characterized in that: The method comprises adding a composite scale inhibitor to cooling water, wherein the composite scale inhibitor comprises the following raw materials in terms of mass percentage: 10-15% of composite copolymer, 5-10% of octylphenol polyoxyethylene ether, 3-6% of glycerol, 2-4% of tetrasodium ethylenediaminetetraacetate, 1-3% of zinc salt, and the remainder is deionized water; The preparation method of the composite copolymer is as follows: Carboxymethyl chitosan, 1-vinyl-3-methylimidazole p-toluenesulfonate and methacryloylethyl sulfobetaine are added to deionized water, stirred evenly, nitrogen is introduced to expel the air, the system is heated to 65-75° C., and then an initiator is added, stirred to react, and after the reaction is completed, cooled to room temperature and vacuum freeze-dried to obtain a composite copolymer.

2. The method according to claim 1, characterized in that The addition amount of the composite antiscalant is 10-40 mg / L.

3. The method according to claim 1, characterized in that: The mass ratio of carboxymethyl chitosan, 1-vinyl-3-methylimidazole p-toluenesulfonate, methacryloylethyl sulfobetaine and initiator is 10-20:4-8:3-6:0.5-1.

4. The method according to claim 1, characterized in that: The initiator is selected from persulfates.

5. The method according to claim 4, characterized in that The persulfate is selected from potassium persulfate, sodium persulfate or ammonium persulfate.

6. The method according to claim 1, characterized in that The stirring reaction temperature is 65-75°C, and the stirring reaction time is 2-4h.

7. The method according to claim 1, characterized in that The zinc salt is selected from zinc nitrate or zinc chloride.

Citation Information

Patent Citations

  • Preparation method of multiple-effect compound type corrosion and scale inhibitor

    CN102838215A

  • Environment-friendly slow-release long-acting scale inhibitor for water treatment

    CN107162222A

  • Phosphorus-free composite scale-corrosion inhibitor, application thereof and treatment method for circulating cooling water

    CN107601684A

  • Efficient corrosion and scale inhibitor and preparation method thereof

    CN118561436A

  • Polymer synthesis and preparation method for water treatment scale inhibition dispersant

    CN118725302A